A critical role for the ATP-sensitive potassium channel subunit KIR6.1 in the control of cerebral blood flow. Issue 10 (October 2019) - Hosford, Patrick S; Christie, Isabel N; Niranjan, Arun; Aziz, Qadeer; Anderson, Naomi; Ang, Richard; Lythgoe, Mark F; Wells, Jack A; Tinker, Andrew; Gourine, Alexander V
KIR 6.1 (KCNJ8) is a subunit of ATP sensitive potassium channel (KATP ) that plays an important role in the control of peripheral vascular tone and is highly expressed in brain contractile cells (vascular smooth muscle cells and pericytes). This study determined the effect of global deletion of the KIR 6.1 subunit on cerebral blood flow, neurovascular coupling and cerebral oxygenation in mice. In KIR 6.1 deficient mice resting cerebral blood flow and brain parenchymal partial pressure of oxygen ( P O2 ) were found to be markedly lower compared to that in their wildtype littermates. However, cortical blood oxygen level dependent responses triggered by visual stimuli were not affected in conditions of KIR 6.1 deficiency. These data suggest that KATP channels containing KIR 6.1 subunit are critically important for the maintenance of normal cerebral perfusion and parenchymal P O2 but play no significant role in the mechanisms underlying functional changes in brain blood flow.